Recognition of Income by Finance Companies. - Comiskey, Eugene E.; Mlynarczyk, F. A. (The Accounting Review, 1968)
Abstract The article focuses on the accounting and other financial reporting practices in some large financial companies. In particular, the methods employed by finance companies in recognizing income on loan transactions have come under dose scrutiny. Financial analysts and investors have become perplexed by the wide range of procedures for recognizing income which are accepted by the accounting profession. This article the more common income-recognition procedures used by finance companies is briefly outlined. In the second section the conformity of these procedures with conventional income measurement theory is considered. Finally, in a concluding section the impact of the income recognition alternatives upon reported income under varying conditions has been examined through the use of computer simulation models. The most important conclusion flows from the effort to test hypothesis. The simulation analysis revealed that differences in income recognized, among the methods commonly used in the industry, were not as great as industry analysts would predict.